A study of InGaP/GaAs/InGaP composite collector double heterojunction bipolar transistor and GaAs delta-doped emitter bipolar junction transistor - Lew, Kim Luong. (2008)
Power amplifiers are critical components in wireless communication systems. The devices chosen for this application must offer improved microwave efficiency, linearity, power handling capacility and potentially manufacturable at low cost. Two devices were systematically studied in this thesis.